PENGEMBANGAN MEDIA PEMBELAJARAN SCIENCE ADVENTURER DALAM MENINGKATKAN MOTIVASI BELAJAR IPAS DI MADRASAH IBTIDAIYAH - Karomah, Ismiyatul; Purwowidodo, Agus (Universitas Islam Lamongan, 2024)
This study aims to develop Science Adventure learning media to improve students' motivation to learn Natural and Social Sciences (IPAS). This research was conducted with development research using the Borg & Gall procedure written in ten stages of development. This research was conducted at MIN 04 Blitar Class V with data collection techniques through observation, interviews, and questionnaires, while data analysis was carried out using the t-test. This study shows that the Science Adventurer learning media is very feasible to use with the validation results from material experts, media experts, and learning experts, each obtaining a score of 94%, 96%, and 94%. This media has also proven effective in improving students' learning motivation, as evidenced by the independent sample t-test, which has a 2-tailed significance value of 0.000. so it can be concluded that the Science Adventure learning media is feasible and effective in improving the motivation to learn IPAS in grade 5 elementary school students